EANM procedure guideline for the treatment of liver cancer and liver metastases with intra-arterial radioactive compounds - Weber, M; Lam, M; Chiesa, C; Konijnenberg, M; Cremonesi, M; Flamen, P; Gnesin, S; Bodei, L; Kracmerova, T; Luster, M; Garin, E; Herrmann, K (European journal of nuclear medicine and molecular imaging, 2022)
Primary liver tumours (i.e. hepatocellular carcinoma (HCC) or intrahepatic cholangiocarcinoma (ICC)) are among the most frequent cancers worldwide. However, only 10-20% of patients are amenable to curative treatment, such as resection or transplant. Liver metastases are most frequently caused by colorectal cancer, which accounts for the second most cancer-related deaths in Europe. In both primary and secondary tumours, radioembolization has been shown to be a safe and effective treatment option. The vast potential of personalized dosimetry has also been shown, resulting in markedly increased response rates and overall survival. In a rapidly evolving therapeutic landscape, the role of radioembolization will be subject to changes. Therefore, the decision for radioembolization should be taken by a multidisciplinary tumour board in accordance with the current clinical guidelines. The purpose of this procedure guideline is to assist the nuclear medicine physician in treating and managing patients undergoing radioembolization treatment. PREAMBLE: The European Association of Nuclear Medicine (EANM) is a professional non-profit medical association that facilitates communication worldwide among individuals pursuing clinical and research excellence in nuclear medicine. The EANM was founded in 1985. These guidelines are intended to assist practitioners in providing appropriate nuclear medicine care for patients. They are not inflexible rules or requirements of practice and are not intended, nor should they be used, to establish a legal standard of care. The ultimate judgment regarding the propriety of any specific procedure or course of action must be made by medical professionals taking into account the unique circumstances of each case. Thus, there is no implication that an approach differing from the guidelines, standing alone, is below the standard of care. To the contrary, a conscientious practitioner may responsibly adopt a course of action different from that set out in the guidelines when, in the reasonable judgment of the practitioner, such course of action is indicated by the condition of the patient, limitations of available resources or advances in knowledge or technology subsequent to publication of the guidelines. The practice of medicine involves not only the science but also the art of dealing with the prevention, diagnosis, alleviation and treatment of disease. The variety and complexity of human conditions make it impossible to always reach the most appropriate diagnosis or to predict with certainty a particular response to treatment. Therefore, it should be recognised that adherence to these guidelines will not ensure an accurate diagnosis or a successful outcome. All that should be expected is that the practitioner will follow a reasonable course of action based on current knowledge, available resources and the needs of the patient to deliver effective and safe medical care. The sole purpose of these guidelines is to assist practitioners in achieving this objective.
Keywords: Dosimetry; Nuclear medicine; 90Y-microspheres; Yttrium Radioisotopes; Liver cancer; Embolization, Therapeutic; Glass microspheres; TheraSphere®; SIR-spheres®; Bile Duct Neoplasms; lidé; Liver Neoplasms; terapeutická embolizace; QuiremSpheres®; nádory jater; hepatocelulární karcinom; Microspheres; Guidelines; Humans; 166Ho-microspheres; Bile Ducts, Intrahepatic; žlučové cesty intrahepatální; mikrosféry; Carcinoma, Hepatocellular; nádory žlučových cest; Resin microspheres; radioizotopy ytria